1992
DOI: 10.1111/j.1095-8649.1992.tb02704.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of increment width and strontium: calcium ratios in otoliths of juvenile rock blackfish, Girella elevata (M.)

Abstract: Otoliths of juvenile Girellu elevufu (M.) were examined to obtain information about the environmental conditions experienced during early life. Patterns of increment deposition and elemental ratios in otoliths were compared in wild fish. A tetracycline experiment indicated that increments were deposited daily in juveniles. Although different patterns in the spacing of increments were found among juveniles collected at different locations and times, the widest increments were always found in the first 40 increm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…This hypothesis is in accordance with the conclusions of Kimura et al (2000) explaining that ambient salinity could be an imprecise measure of the contribution of Sr incorporation on the otolith edge. Previous studies could also demonstrate that the Sr:Ca ratio did not respond directly to the exposure to Sr variation in the environment (Gallahar and Kingsford 1992;Elsdon and Gillanders 2005). This therefore suggested that there is a short duration before the otolith responds to environmental conditions, but this lag time duration for elemental incorporation within the otolith is unknown (Elsdon and Gillanders 2005).…”
Section: Uses Of Individual Means Of Sr:ca Ratiosmentioning
confidence: 93%
“…This hypothesis is in accordance with the conclusions of Kimura et al (2000) explaining that ambient salinity could be an imprecise measure of the contribution of Sr incorporation on the otolith edge. Previous studies could also demonstrate that the Sr:Ca ratio did not respond directly to the exposure to Sr variation in the environment (Gallahar and Kingsford 1992;Elsdon and Gillanders 2005). This therefore suggested that there is a short duration before the otolith responds to environmental conditions, but this lag time duration for elemental incorporation within the otolith is unknown (Elsdon and Gillanders 2005).…”
Section: Uses Of Individual Means Of Sr:ca Ratiosmentioning
confidence: 93%
“…In other words, ontogenetic changes in otolith elemental composition are assumed not to exist. Yet such changes have been clearly documented, even in fish held under constant environmental condit~ons (Gallahar & Kingsford 1992, Fowler et al 1995b. As a result, observed trends in concentration across an otolith could reflect either a shift in the fish's environment, an age-related change in incorporation rate independent of the environment, or both.…”
Section: Migration Historymentioning
confidence: 99%
“…This latter assumption is an interesting one, since it implies that the rate of elemental incorporation is independent of the rate of calcification, contrary to our current understanding of trace element incorporation. The few studies that have examined these assumptions in otoliths reported varying levels of consistency in minor element concentrations along a variety of transects within an otolith, or between paired otoliths (Gallahar & Kingsford 1992, Gunn et al 1992, Secor 1992, Thresher et al 1994). It was not clear from these studies whether the variation was real, or if it merely reflected difficulties in aligning the microprobe beam to the appropriate increment.…”
Section: Sampling and Analysesmentioning
confidence: 99%
“…A greater amount of Sr was found in otoliths of recruits from rocky reef than in recruits from seagrass habitat. High Sr levels have previously been correlated with high salinity levels (Radtke et al 1988, Kalish 1990, Secor 1992, Coutant & Chen 1993 and low temperatures (Radtke et al 1990, Townsend et al 1992, but see Kalish 1989, Gallahar & Kingsford 1992. Large plumes of low density water are known to extend out of Botany Bay (Kingsford & Suthers 1994), meaning that estuarine seagrass habitats are likely to be exposed to lower salinity waters than coastal rocky reefs.…”
Section: Eiemental Compositior Of Ctoliths Collected From Recruitsmentioning
confidence: 99%